Understanding the requirements and barriers to providing Post-Trial Access (PTA): A review of continued access to effective medicine - Mthembu, Xoliswa (University of the Witwatersrand, Johannesburg, 2024)
Clinical trials are essential in establishing the safety and efficacy of investigational products and are a mandatory requirement for the registration of a new medicine. Additionally, clinical studies offer access to new therapies, innovative treatments or more effective treatments which may not be readily accessible to the general population. Clinical trial participants receive investigational medicine during the study conduct phase as a study benefit and as compensation for their voluntary participation. In resource-limited countries, this may be the only option available to access new and effective medicine. Therefore, continued treatment access becomes of greater value. However, providing PTA presents ethical considerations which need to be addressed. The provision of PTA to effective medicine can be viewed as an inducement to join a study and creates inequalities between diseased patients, as it excludes other diseased patients who did not participate in the study or patients who were excluded from participation in the study. However, prior to addressing these controversies, it is necessary to establish first whether clinical trial participants have a moral claim to PTA provision. This report seeks to establish the moral requirement for PTA provision to address the ethical issues around providing continued access to effective medicines outside clinical trial settings. The first two chapters will focus on discussing the evolution of clinical trials, highlighting the ethical issues surrounding continued access to effective investigational products. The principles of bioethics will be discussed in detail in Chapter 2 to draw out the moral claims which mandate the requirement to provide PTA to efficacious medical therapy offered during the study. In Chapter 3, I will argue for the moral requirement for providing PTA using the principles of bioethics as a framework. In Chapter 4, I will discuss the challenges and PTA solutions. In my conclusion, I will reiterate my support for the mandatory requirement and implementation of PTA until the Investigational Product is commercially available and accessible to all trial participants, emphasising the importance of this stance.
A research report Submitted in fulfillment of the requirements for a Masters in Applied Ethics for Professionals, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Post-Trial Access; Clinical trials; Bioethics; Principles of Principlism and Ethical Justification; SDG-3: Good health and well-being